Prevalence and characterization of Yersinia enterocolitica isolated from retail foods in China. (March 2016) - Ye, Qinghua; Wu, Qingping; Hu, Huijuan; Zhang, Jumei; Huang, Huixian
Abstract: Yersinia enterocolitica is an important food-borne enteropathogen that causes gastrointestinal syndromes. The aims of this study were to identify Y. enterocolitica in food samples in China, and to assess the pathogenic potential and antimicrobial resistance, and to characterize the genotypes of the isolates. From July 2011 to May 2014, a total of 2320 food samples were obtained, and 47 (2.03%) were found positive for Y. enterocolitica, while 706 retail-level ready-to-eat products and 249 vegetable samples were negative. A total of 58 Y. enterocolitica strains were isolated. All isolates belonged to biotype 1A, and the primary serotype was O:8. All strains lacked the ail, virF, ystA, and ystC virulence genes, but harbored the ystB, fepD, ymoA, fes, and sat genes. All 58 strains were sensitive to kanamycin and sulfonamide, but were resistant to two or more antibiotics. Most of the strains expressed the β-lactamase genes; the presence of blaA and blaB was detected in 97% and 100% of isolates, respectively. Many strains were resistant to trimethoprim/sulfamethoxazole (79.3%), ampicillin (91.4%), and cephalothin (91.4%). The 58 strains were grouped into three clusters and one singleton by enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) at a similarity coefficient of 70%, and each cluster was largely organized by geographical region. This study provides a valuable accounting of the prevalence of Y. enterocolitica from a nationwide survey of foods in China, and highlights the seasonal effects of Y. enterocolitica prevalence in foods in China for the first time. Highlights: Y. enterocolitica prevalence in retail foods was higher in winter than in summer. Y. enterocolitica strains with the bioserotype 1A/O:8 dominated in foods. The predominant genotype was: ystB + fepD + ymoA + fes + sat + inv + hrep + fepA + ail − virF − ystA − ystC − . All Y. enterocolitica isolates were multidrug resistant. ERIC-PCR subtyping were used for genetic diversity analyses.